We're growing together - Ransom, Candice F., 1952-; Wright-Frierson, Virginia (New York : Bradbury Press, 1993)
A girl discovers that it takes time for her to adjust to her new stepfather and that he must also learn to adjust to her.
Booklist
Horn Book
Kirkus Review
2.3
K-3
Keywords: Stepfathers -- Fiction; Remarriage -- Fiction; Country life -- Fiction; Stepfathers -- Fiction; Country life -- Fiction; Remarriage -- Fiction